Corporate Participation in ESG Ratings and the Accuracy of Analysts’ Surplus Forecasts: Based on the Perspective of Green Finance Policy Implementation - Zhi, Huanyu (Transactions on Economics, Business and Management Research, 2024)
The article takes China’s A-share listed companies from 2012to 2022 as the research target, using the different-in-difference model, and investigate the impact of ESG rating on the accuracy of analysts’ forecast accuracy under China’s green finance policies. This study finds that under green finance policies, ESG rating companies significantly have higher analysts’ forecast accuracy, which is manifested in the reduction of analysts’ forecast error and optimism bias. In terms of the mechanism, ESG-rated companies are more likely followed by security analysts and are willing to provide better quality of information disclosure, and thus have higher analysts’ forecast accuracy. This study also examines firm heterogeneity. Under the green finance policies, the positive impact of ESG rating on the analysts’ forecast accuracy is more significant in non-state-owned enterprises and enterprises in ESG-sensitive industries.